Conservation Biology in Sub-Saharan Africa - Wilson, John W.; Primack, Richard B.; Open Textbook Library (Open Textbook Library, 2019)
Conservation Biology in Sub-Saharan Africa comprehensively explores the challenges and potential solutions to key conservation issues in Sub-Saharan Africa. Easy to read, this lucid and accessible textbook includes fifteen chapters that cover a full range of conservation topics, including threats to biodiversity, environmental laws, and protected areas management, as well as related topics such as sustainability, poverty, and human-wildlife conflict. This rich resource also includes a background discussion of what conservation biology is, a wide range of theoretical approaches to the subject, and concrete examples of conservation practice in specific African contexts. Strategies are outlined to protect biodiversity whilst promoting economic development in the region.
1. What is Conservation Biology? -- 2. Introduction to Sub-Saharan Africa -- 3. What is Biodiversity? -- 4. Why Should We Protect Biodiversity? -- 5. The Scramble for Space -- 6. Our Warming World -- 7. Pollution, Overharvesting, Invasive Species, and Disease -- 8. Extinction Is Forever -- 9. Applied Population Biology -- 10. Conserving Ecosystems -- 11. Preventing Extinctions -- 12. Biodiversity and the Law -- 13. The Importance of Protected Areas -- 14. Conservation on Unprotected Lands -- 15. An Agenda for the Future
In English.
Description based on print resource
Keywords: Biology -- Textbooks